The impact of the aesthetic style strategy in developing coordination thinking and aesthetic experience among students of the Department of Art Education in the subject of pictorial composition - Fatima Muhammad Abdullah ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Education is considered one of the necessities of the foundations of building and culture of society through human development and building it in the correct methodological manner. The research problem can be identified by the following question:What is the effect of the aesthetic style on developing the aesthetic experience of the students of the Department of Art Education in the subject of pictorial composition?The aim of the research was to reveal the impact of the aesthetic style in developing the aesthetic experience of the students of the Department of Art Education in the subject of pictorial composition.The research tools were built, the aesthetic experience test, which included (30) items, the validity and reliability were drawn, and the research results, sources, and appendices were extracted.